2014
DOI: 10.5539/ijps.v6n1p33
|View full text |Cite
|
Sign up to set email alerts
|

Elite Disability Sport Coaches’ Views on Sport Psychology

Abstract: Although the coach is a key element in the psychological preparation of the athletes, few is known about what coaches from disability sport context think about the importance of psychological preparation. Therefore, this study aimed to explore: 1) the educational background of disability sport coaches, 2) the perceptions of the coaches on the importance of psychological preparation for their athletes, and 3) the opinions of the coaches regarding the role of sport psychologists. Semi-structured interviews were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It should be mentioned, however, that for most coaches, this is their additional work. With this in mind, and taking into account the opinions of Bastos et al [4] and Martin and Whalen [5] about the significant role of both female and male coaches in sports professionalization and achievement of the maximum potential of elite players with disabilities, it can be concluded that the further development of Polish professional sport raises many concerns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be mentioned, however, that for most coaches, this is their additional work. With this in mind, and taking into account the opinions of Bastos et al [4] and Martin and Whalen [5] about the significant role of both female and male coaches in sports professionalization and achievement of the maximum potential of elite players with disabilities, it can be concluded that the further development of Polish professional sport raises many concerns.…”
Section: Discussionmentioning
confidence: 99%
“…The differences were in its main part, which included fewer items (8 questions). The questions were semi-open (4), open (3) and closed (1). Comparing it with the questionnaire for athletes of national Paralympic team, there were no questions about the rights and obligations of players appointed to the national team and about coaches who athletes with disabilities would like to work with.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although researchers in able-bodied sport have examined coaches' views of psychological skills and the value of sport psychologists, only one group of researchers have targeted similar questions in disability sport. In a interview study of ten Portuguese elite disability sport coaches, Bastos and colleagues established two important themes related to sport psychology (Bastos, Corredeira, Probst, & Fonseca, 2014).…”
Section: )"mentioning
confidence: 99%
“…However, these outcomes were almost exclusively attributed to athletes with limitations that enabled them to independently cope with most daily tasks, such as those with paraplegia or lower-limb amputation. In contrast, some authors discuss the specific difficulties of individuals with severe disabilities (e.g., transportation, dependence on others for performing sports and daily tasks, psychosocial vulnerability) and recommend accounting for these unique circumstances [9][10][11]. So far, very few (if any) studies have identified sports or other interventions that may help adults with severe physical disability improve their psychosocial functioning.…”
Section: Introductionmentioning
confidence: 99%